Origin of IceCube's Astrophysical Neutrinos: Autocorrelation, Multi-Point-Source and Time-Structured Searches - Bernhard, Anna (Technical University of Munich, 2015)
The IceCube neutrino observatory build in the Antarctic ice offers unique opportunities in studying high energy neutrino emission from galactic and extra-galactic sources and could give invaluable information about the origin of cosmic rays. In 2013, IceCube discovered the first astrophysical neutrinos, but their origin remains unclear, which motivates additional searches. In this work three analyses for a small-scale clustering of neutrino events, based on a two-point correlation function are presented. Das IceCube Neutrino Observatorium im antarktischen Eis bietet einzigartige Möglichkeiten für die Erforschung von Neutrino Emission aus galaktischen und extra-galaktischen Quellen und könnte wertvolle Informationen über den Ursprung der kosmischen Strahlung liefern. In 2013 entdeckte IceCube die ersten astrophysikalischen Neutrinos, deren Ursprung allerdings noch unklar ist. Diese Arbeit beinhaltet drei Analysen für eine kleinskalige Korrelation von Neutrinos basierend auf einer Zweipunkt-Korrelationsfunktion.